Artificial Intelligence for Signal Processing and Wireless Communication (De Gruyter Series on the Applications of Mathematics in Engineering and Information Sciences ,, 2022)
This book focuses on artifi cial intelligence in the field of digital signal processing and wireless communication. The implementation of machine learning and deep learning in audio, image, and video processing is presented, while adaptive signal processing and biomedical signal processing are also explored through DL algorithms, as well as 5G and green communication. Finally, metaheuristic algorithms of related mathematical problems are explored.